Nurse Practitioner Role Enactment in Community Palliative Care - Halabisky, Brenda (Université d'Ottawa / University of Ottawa, 2022)
Abstract Background: Access to adequate palliative care has been identified as a challenge globally, in Canada, and in the province of Ontario. While pockets of excellence exist, there is a national call for allocation of resources and implementation of best practices to improve the care for individuals with life limiting illnesses. Furthermore, the location of care along with a desire for dying at home has shifted responsibility onto family members often without the equivalent shift in community resources to meet patient and family needs. To respond to issues of access and quality, nurse practitioners (NPs) have been increasingly added to diverse practice settings across the globe and research showing how they are contributing to diverse care settings. As a strategy to improve community palliative care locally, NPs have been added to community settings in Ontario. However, because NPs are new to palliative care settings little is known about how NPs enact their role within this unique context. NP role enactment is defined as the actual activities that NPs engage in that constitute their daily work. Aim: The purpose of this study is to better understand how NPs enact their role as consultants in a specific community palliative care setting in Ontario. Methodology and Methods: A focused ethnography was conducted in one specific geographic health administration region of Ontario between July of 2018 and October of 2020. A convenience sample was used recruiting NPs from one community palliative care consultation team. Data collection methods included observation (487.5 hrs over 89 discrete observation sessions, distributed across 7 study participants), fieldnotes and semi-structured interviews with participants (n = 7 NPs). Results: The NPs enacted their role with patients by formulating relationships, that for them, facilitated a deeper understanding of the patient and family situation, strengths, challenges and desires. Using conversations and conversational skills to have difficult and important conversations, NPs facilitated future planning for patients. Conversations also included addressing questions about MAiD, which were nuanced and often about more than MAiD, also addressing fears of suffering and uncertainty. The NPs used advanced clinical judgment and skill to diagnose and treat complex and difficult to manage symptoms and supported families to understand complicated medication regimes. Valuing their role as educators, the NPs supported their peers by offering teaching and providing clinical support in complex care scenarios. Pull together disparate and loosely connected care providers, NPs created a shared understanding of patient needs. Deficiencies in community care resourcing and organization made it difficult at times for NPs to facilitate continuity in care or to build capacity. The NPs often navigated an environment where nursing staffing was transient, inconsistent and overextended and where physicians were inconsistently available to support rapidly evolving situations. Conclusion: Findings suggest that NPs have an important role to play in supporting patients and families as well as supporting their nursing and physician colleagues. Furthermore, the broader system would benefit from embedding palliative care NPs more systematically. However, broader structural enhancements like shared communication and documentation mechanisms and adequate staffing across care settings need to be addressed to maximize the potential contributions NPs are able to offer.
Keywords: Nurse Practitioner; Advanced Practice Nursing; Role Enactment; Community Palliative Care; Palliative Care; Community Nursing